2011
DOI: 10.5028/jatm.2011.03019610
|View full text |Cite
|
Sign up to set email alerts
|

The use of molecular spectra simulation for diagnostics of reactive flows

Abstract: The C 2 * radical is used as a system probe tool to the reactive flow diagnostic, and it was chosen due to its large occurrence in plasma and combustion in aeronautics and aerospace applications. The rotational temperatures of C 2 * species were determined by the comparison between experimental and theoretical data. The simulation code was developed by the authors, using C++ language and the object oriented paradigm, and it includes a set of new tools that increase the efficacy of the C 2 * probe to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In 1950, however, Gaydon found a difference with respect to the thermodynamic temperature when using the spectrum of OH * to measure the temperature of a hydrocarbon flame [22]. Additionally, in 2011, Passaro et al observed the high rotation temperature phenomenon when measuring the combustion temperature of liquefied gas based on the C 2 * emission spectrum [23]. The main reason for the observed differences in these cases is that the number distribution of the excited state particles has not reached its equilibrium state, and the rotational energy level is thus over-distributed.…”
Section: Introductionmentioning
confidence: 99%
“…In 1950, however, Gaydon found a difference with respect to the thermodynamic temperature when using the spectrum of OH * to measure the temperature of a hydrocarbon flame [22]. Additionally, in 2011, Passaro et al observed the high rotation temperature phenomenon when measuring the combustion temperature of liquefied gas based on the C 2 * emission spectrum [23]. The main reason for the observed differences in these cases is that the number distribution of the excited state particles has not reached its equilibrium state, and the rotational energy level is thus over-distributed.…”
Section: Introductionmentioning
confidence: 99%